Disparity in Jurisprudence on Breaking a Marriage Promise - Jeremia Alexander Wewo (Arena Hukum, 2024)
The study aims to analyse the differences in judicial decisions that classify breaking a marriage promise judgements as either breach of promise or wrongful acts against the Law and the legal implications of these differing judgments in breaking a marriage promise cases. The research adopts a normative legal approach. The findings reveal that the basis for judicial consideration in categorising cases as either breach of promise or wrongful acts varies significantly, as illustrated in two cases. In Case Number 8/Pdt.G/2019/PN.Mme, the judge ruled that the agreement between the petitioner and the respondent created a binding legal consequence, whereby the wedding vows established a binding commitment between the parties that could not be nullified, requiring good faith in fulfilment. Conversely, in Case Number 295/Pt.G/2020/PNKpg, the judge classified the respondent’s unfulfilled promise to marry the petitioner as wrongful, thus breaching the law. These differences in legal reasoning lead to legal uncertainty and the absence of legal order. The study suggests that a unified approach is essential for handling cases involving broken marriage promises, so that there is a need for the uniformity of the judge’s ruling in dealing with the marriage promises and this will be realized through the formulation of the provisions in the Circular Letter of the Supreme Court.